Advertisement and territorial calls of Brachycephalus pitanga (Anura: Brachycephalidae) - de Araújo, Carlos B.; Guerra, Tadeu J.; Amatuzzi, Maria Clara O.; Campos, Leandro A. (Zootaxa, 2012)
The genus Brachycephalus Fitzinger, 1826 comprises 17 tiny species, eight of which were described only in the past 10 years (Frost 2012). Vocal communication is still poorly studied in this group, and despite its importance for taxonomic studies (e.g. Padial & De La Riva 2009) only two species of the group have had their calls described (Pombal et al. 1994; Verdade et al. 2008).